(untitled) (International Journal of Geoscience, Engineering and Technology, 2023)
In Civil Engineering, the structural design, which includes foundations, columns, beams, and slabs, must be developed to ensure that the criteria for use and serviceability are met. Foundations, in particular, are responsible for transmitting the loads from the structure to the ground on which it is supported. In this regard, this work aims to present a tool in the form of an interactive and automated spreadsheet to assist in the selection of the type of foundation to be used in the project. Additionally, the factors that influence the choice of specific types of foundations will be discussed. The spreadsheet was created using Microsoft Excel, based on normative criteria and semi-empirical equations. The tool proved to be an efficient resource, facilitating the decision-making process. It is worth noting that each situation presents inherent peculiarities, making the foundation type selection process unique, and it is up to the designer to analyze them and make the appropriate choices.